Penyembuhan luka sayatan menggunakan krim ekstrak teripang laut dan kunyit - Alpayet, Rahmat; Mustika, Aulia Andi; Rahma, Anisa; Andriyanto; Sutardi, Lina Noviyanti (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2023)
Background: Skin is the outermost layer that covers and protects the body and is vulnerable to trauma, such as wounds. Turmeric and sea cucumbers are known to have properties in wound healing. Objective: This study aims to determine the effectiveness of a mixture of sea cucumber and turmeric extracts in the form of a cream to heal incision wounds in rats. Methods: Twenty-five male white rats, Sprague Dawley strain, and body weights of 250–300 g were anesthetized, and their skins were slashed. The rats were divided into five groups, namely negative control (wounds without treatment), positive controls (wounds treated with Bioplacenton® topically), and three treatment groups (wounds treated with sea cucumber and turmeric extract cream with concentrations of 0.5%, 1%, and 2% topically). Wound healing parameters were observed daily, namely accelerated wound closure and inflammation reduction. Data were analysed descriptively and tested using the non-parametric Kruskal-Wallis’s test. Results: The results showed that the wounds closed completely in all treated groups. Healing time in the group receiving treatment (positive control and concentration treatment of 0.5%, 1%, and 2% were 8.3 ± 1.5 days, 10.3 ± 0.6 days, 9.3 ± 0 .6 days, and 8.3 ± 1.5 days, respectively) faster than the healing time of the group that did not receive treatment (negative control was 12.6 ± 0.6 days). Conclusion: This study showed that sea cucumber and turmeric extract cream has the potential and is effective for wound healing and can be used as an alternative for wound treatment.